2016
DOI: 10.1038/nchembio.2116
|View full text |Cite
|
Sign up to set email alerts
|

A reactivity-based probe of the intracellular labile ferrous iron pool

Abstract: Improved methods for studying intracellular reactive iron(II) are of significant interest for studies of iron metabolism and disease relevant changes in iron homeostasis. Here we describe a highly-selective reactivity-based probe in which Fenton-type reaction with intracellular labile iron(II) leads to unmasking of the aminonucleoside puromycin. Puromycin leaves a permanent and dose-dependent mark on treated cells that can be detected with high sensitivity and precision using the high-content, plate-based immu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
177
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 128 publications
(188 citation statements)
references
References 46 publications
10
177
0
1
Order By: Relevance
“…34 These initial studies with TRX-PURO also confirmed that labile iron pools are generally augmented in cancer cells when compared to nontumorigenic cells. 34 Our findings thus suggested that the TRX scaffold might indeed be applied to produce a novel class of TAPs for cancer chemotherapy.…”
Section: Introductionmentioning
confidence: 77%
See 1 more Smart Citation
“…34 These initial studies with TRX-PURO also confirmed that labile iron pools are generally augmented in cancer cells when compared to nontumorigenic cells. 34 Our findings thus suggested that the TRX scaffold might indeed be applied to produce a novel class of TAPs for cancer chemotherapy.…”
Section: Introductionmentioning
confidence: 77%
“…This process occurs with high efficiency and ferrous-iron selectivity in mammalian cancer cell lines, as described recently. 34 …”
Section: Introductionmentioning
confidence: 99%
“…The former can be detected using inductively coupled plasma-MS or calcein AM quenching, as well as other specific iron probes (Hirayama and Nagasawa, 2017; Spangler et al, 2016), while the latter can be detected using phosphatidylcholine hydroperoxide reduction in cell lysates using LC-MS (Yang et al, 2014). …”
Section: Commonly Used Reagents For Studying Ferroptosismentioning
confidence: 99%
“…In ICL-1, we caged D-aminoluciferin with an Fe 2+ -reactive endoperoxide trigger (15,17,51) inspired by antimalarial agents that exhibit Fe 2+ -dependent pharmacology (52,53). ICL-1 was designed to undergo metal-and redox-specific Fe 2+ -dependent cleavage to generate D-aminoluciferin, which can interact with the firefly luciferase enzyme to produce red light output through a catalytic bioluminescent reaction.…”
Section: Significancementioning
confidence: 99%
“…In this regard, detection of iron with both metal and oxidation state specificity is of central importance, because while iron is stored primarily in the ferric oxidation state, a ferrous iron pool loosely bound to cellular ligands, defined as the labile iron pool (LIP), exists at the center of highly regulated networks that control iron acquisition, trafficking, and excretion. Indeed, as a weak binder on the Irving-Williams stability series (13), Fe 2+ provides a challenge for detection by traditional recognition-based approaches (14), and as such we (15)(16)(17) and others (18)(19)(20) have pursued activity-based sensing approaches to detect labile Fe 2+ stores in cells (21)(22)(23)(24)(25). These tools have already provided insights into iron biology, as illustrated by the direct identification of elevations in LIPs during ferroptosis (26,27), an emerging form of cell death, using the ratiometric iron indicator FIP-1 (15).…”
mentioning
confidence: 99%